ANALYSIS OF SOCIAL ASSISTANCE FUNDS ON THE FACILITATION PROGRAM IN ORPHANAGES/NURSING HOMES IN SOCIAL SERVICE OFFICE OF BANDUNG REGENCY - Nulhaqim, Soni Akhmad; Widianingsih, Ida; Hadiyanto, Ferry; Mulyawan, Rahman; Moenardy, Dwi Fauziansyah (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Social Service Office of Bandung Regency has a mission to carry out various social assistance programs distributed directly to the community, one of which is to issue various social assistance programs. The social assistance carried out by the Social Service Office of Bandung Regency aims to alleviate poverty and responding to various social issues in the community.This research uses a qualitative design as it systematically describes how an effective monitoring and evaluation system is implemented in the social assistance program at the Social Service Office of Bandung Regency. The research technique is interviews, observations, and documentation studies of resource persons.The results show that the financing assistance for the orphanage/nursing home facilitation program from 2016, 2017, and 2018 fluctuated according to the conditions in the field. However, assistance for orphanages/nursing homes is still focused on improving the skills of trainers and educators. While activities such as renovating buildings and facilities as well as increasing the operational costs of the orphanages/nursing homes have not been carried out in 2016, 2017, and 2018.This study recommends that cooperation between the private sector (through CSR) and the Social Service Office or the orphanages/nursing homes is needed. Therefore,the social assistance program in the orphanage/nursing home facilitation program can be carried out better.